Persepsi Mahasiswa Terhadap Kualitas PSAK No.22 (Revisi Adopsi 2010) Hasil Adopsi IFRS - Isti Rahayu; Redita Oksadila (Jurnal Aplikasi Bisnis, 2017)
This research aims to reveal the quality perceive oj PSAK 22 (revised 2010), it also tests whether there are any differences in quality perceive of PSAK 22 (revised 2010) between students who have read and have not read it. PSAK 22 (revised 2010) resulted in the Adoption of IFRS. The research objects are the students of Accounting Department of Economics Faculty of Universitas Islam Indonesia who have Undertaken subjects of Advanced Accounting and Business Combination Accounting. The study proves that the students perceive the quality of PSAK 22 (revised 2010) do not meet the qualitative criteria of accounting standards. In addition it also shows that there are differences in quality perceive of PSAK 22 (revised 2010) between students who have read and have not read it.